2019
DOI: 10.23736/s0022-4707.18.08579-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on posterior circumflex humeral artery pathology: sports and professions at risk and associated risk factors

Abstract: This provisional PDF corresponds to the article as it appeared upon acceptance.A copyedited and fully formatted version will be made available soon. The final version may contain major or minor changes. Subscription: Information about subscribing to MinervaMedica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to: journals.dept@minervamedica.it -journals2.dept@minervamedica.it -ABSTRACT INTROD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Hence, an anthropometric study might be needed to determine the landmarks for a PCHA originating from the SSA. Furthermore, understanding this irregularity for other uncommon surgeries, such as axillary tissue flap formation and axillary scar release, may benefit surgeons [ 13 ]. While surgeons must have a firm grasp of basic anatomy often presented in textbooks, anatomical irregularities are extremely common and should also be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, an anthropometric study might be needed to determine the landmarks for a PCHA originating from the SSA. Furthermore, understanding this irregularity for other uncommon surgeries, such as axillary tissue flap formation and axillary scar release, may benefit surgeons [ 13 ]. While surgeons must have a firm grasp of basic anatomy often presented in textbooks, anatomical irregularities are extremely common and should also be studied.…”
Section: Discussionmentioning
confidence: 99%
“… 4 In a systematic review by Kraan et al., 41 (61%) of 67 cases were seen in individuals who play volleyball, followed by those who play baseball with 13 (19%). 13 van de Pol et al. reported symptoms of finger artery thrombosis with PCHA pathological lesions (during practice or competition) in 99 elite Dutch volleyball players.…”
Section: Discussionmentioning
confidence: 99%
“…However, the anatomical course of the PCHA is additionally of clinical importance in relation to sports injuries. Kraan et al, [26] reported in a systematic review in relation to PCHA aneurysms, which can lead to ischemic emboli in the upper limb, that an anatomical variation may be protective. If the PCHA is running through the quadrangular space, this poses a risk of the artery being damaged by repetitive muscle contraction as it passed through the narrow space.…”
Section: Tablementioning
confidence: 99%